Institutional Uncertainty and European Social Union : Impacts on Job Creation and Destruction in the CEECs - Ansgar Belke; Matthias Göcke; Martin Hebler (Institute for the Study of Labor (IZA), 2004)
With the extension of its competence for social policy legislation in the Maastricht and Amsterdam treaties, the EU has adopted a significantly new social dimension in the past ten years. According to the Copenhagen criteria, the CEEC candidate countries have to adopt the former via the acquis communautaire. This paper discusses the effect of an adoption of this EU social law on future labor market performance in the CEECs. For this purpose, we model and investigate the impact of institutional uncertainty (and of its elimination) on job creation and job destruction in the CEEC candidate countries. We conclude that structural change on CEEC labor markets tends to be fostered via reducing institutional uncertainty. However, these kinds of benefits of the adoption of the acquis have to be weighed against the danger that the adoption of inefficient EU social and labor policy regulations imposed by the acquis might also entail significant risks for employment in the CEECs similar to those which have materialized in the former EU. This rather pessimistic view can be substantiated based on a public choice analysis of why the old EU members will want to impose the Social Charter even though it will harm the new members. These risks consist of a significant increase in hiring and firing costs and of higher wage rates. Based on a simple option value analysis, we investigate and evaluate the trade-off between lower institutional uncertainty and higher employment costs induced by the adoption of the acquis.
Keywords: P26; J23; D81; 330; EU enlargement; real option approach; social union; institutional uncertainty; EU-Sozialpolitik; EU-Erweiterung; Arbeitsmarktflexibilisierung; Risiko; Realoption; Beschäftigungseffekt; Theorie; Osteuropa